The Importance of Social Entrepreneurship Orientation and Social Salience on Hospital Performance: The Mediating Role of Business Planning - Diana Haira; Ria Nelly Sari; Novita Indrawati (JASF: Journal of Accounting and Strategic Finance, 2022)
The purpose of this study is to discover the internal resources that have a significant impact on the performance of social enterprises. This study is quantitative research. The population in this study is a hospital in Pekanbaru City, Riau Province, Indonesia. Twenty-nine hospitals were taken as samples for the study using a purposive sampling technique. SEM-PLS was used to evaluate the data obtained. The result showed that hospital performance was significantly influenced by social entrepreneurship orientation and business planning. Although social salience has a considerable impact on the hospital's social performance, it has no direct impact on its financial performance. This finding reflects the hospital's current state as a complicated organization with challenges balancing financial and social performance. Business planning acts as a mediator that significantly affects the relationship between resources and hospital performance. Therefore, the complexity of the hospital hybrid business requires business planning to balance the two performances. These findings can help hospital management determine the hospital’s strategic direction and provide model guidance for hospital investors, policymakers, and researchers.